Establishment of the multi-component bone-on-a-chip: to explore therapeutic potential of DNA aptamers on endothelial cells - Fan, Xiaoyu; Yan, Yuhan; Zhao, Lianhui; Xu, Xin; Dong, Yiyang; Sun, Wei (Frontiers in Cell and Developmental Biology, 2023)
Background: Despite great efforts to develop microvascular bone chips in previous studies, current bone chips still lacked multi-component of human-derived cells close to human bone tissue. Bone microvascular endothelial cells (BMECs) were demonstrated to be closely related to the glucocorticoid (GC)-induced osteonecrosis of the femoral head (ONFH). Tumor necrosis factor-alpha (TNF-α) aptamer has been proved to bind to its receptor and block cascade activities. Objective: There are two main objectives in this study: 1) to establish a multi-component bone-on-a-chip within the microfluidic system in vitro, 2) to explore the therapeutic potential of TNF-α aptamer on BMECs in the GC-induced ONFH model. Methods: Histological features of clinical samples were analyzed before BMECs isolation. The functional bone-on-a-chip consists of the vascular channel, stromal channel and structure channel. GC-induced ONFH model was established based on the multi-component of human-derived cells. Truncation and dimerization were performed on a previously reported DNA aptamer (VR11). BMECs apoptosis, cytoskeleton and angiogenesis status in the ONFH model were observed by the TUNEL staining and confocal microscope. Results: The multi-component of BMECs, human embryonic lung fibroblasts and hydroxyapatite were cultured within the microfluidic bone-on-a-chip. TNF-α was found up-regulated in the necrotic regions of femoral heads in clinical samples and similar results were re-confirmed in the ONFH model established in the microfluidic platform by detecting cell metabolites. Molecular docking simulations indicated that the truncated TNF-α aptamer could improve the aptamer-protein interactions. Further results from the TUNEL staining and confocal microscopy showed that the truncated aptamer could protect BMECs from apoptosis and alleviate GC-induced damages to cytoskeleton and vascularization. Conclusion: In summary, a microfluidic multi-component bone-on-a-chip was established with ‘off-chip’ analysis of cell metabolism. GC-induced ONFH model was achieved based on the platform. Our findings provided initial evidence on the possible potentials of TNF-α aptamer as a new type of TNF-α inhibitor for patients with ONFH.